N1-Substituted benzimidazole scaffold for farnesoid X receptor (FXR) agonists accompanying prominent selectivity against vitamin D receptor (VDR). Issue 14 (15th July 2020) - Masuda, Arisa; Gohda, Keigo; Iguchi, Yusuke; Fujimori, Ko; Yamashita, Yukiko; Oda, Keisuke; Une, Mizuho; Teno, Naoki
Graphical abstract: Abstract: As a cellular bile acid sensor, farnesoid X receptor (FXR) participates in regulation of bile acid, lipid and glucose homeostasis, and liver protection. With respect to the bone metabolism, FXR positively regulates bone metabolism through both bone formation and resorption of the bone remodeling pathways. Some of FXR agonists possessing isoxazole moiety are undergoing clinical trials for the treatment of non-alcoholic steatohepatitis. To date, therefore, the activation of FXR leads to considerable interest in FXR as potential therapeutic targets. We have identified a series of nonsteroidal FXR agonists bearing N 1 -methyl benzimidazole and isoxazole moieties that are bridged with aromatic derivatives. They showed affinity to FXR, but also weak affinity toward the vitamin D receptor (VDR) that involves regulation of calcium and phosphate homeostasis and is activated by bile acids. The deployment of FXR agonists without activity against VDR as off-target is therefore crucial in the development of FXR ligands. Our efforts focusing on increasing the agonist properties towards FXR led to the discovery of 19, which activates FXR at and below nanomolar levels (EC50 = 26.5 ± 10.5 nM TR-FRET and 0.8 ± 0.2 nM luciferase, respectively) and functions as a FXR agonist: the affinity toward FXR over eight nuclear receptors, including VDR [IC50 (VDR) / EC50 (FXR) > 5000] and TGR5, effects FXR target genes, and activates bone morphogenetic protein-2-induced differentiation of mouse bone marrow-derived mesenchymal stem cell-like ST2 cells into osteoblast.